Setting Free the Mother Bird: On Reading a Strange Text - Muers, Rachel (Modern theology, 2006)
Deuteronomy 22:6-7 has been used in recent theological discussions of environmental ethics. Earlier traditions of interpretation (Jewish and Christian) suggest the further possibility of reading it as a text about how to read texts and about the nature and function of law. This article examines, and offers a contemporary Christian reappropriation of, these traditions of interpretation. The focus is on how the confrontation with the vulnerable other as a locus of divine revelation interrupts and transforms relations of use and exploitation. It is argued that in a Christian reading of the bird's-nest precept Christ "does what the precept does".